2020
DOI: 10.3934/biophy.2020019
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Thermal investigation of montmorillonite/BSA by Fourier Transform InfraRed Spectroscopy measurements

Abstract: <abstract> <p>This paper reports the analysis of the intramolecular OH stretching band obtained by Fourier Transform Infrared (FTIR) spectroscopy measurements. In order to characterize the effect of montmorillonite on the properties of Bovine Serum Albumin (BSA) the two-state model is adopted for the analysis of the OH stretching band. We assume that the OH stretching can be divided into two different states of inter-molecular bonding. The results of this experimental work confirm that the montmori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The low enhancing efficiency of Al_MMT treated with Trp can be explained by the low absorption of Trp of MMT due to the counterbalance of either positive (-NH 2 ) and negative (-COOH) groups in the aminoacidic structure. On the contrary, different studies showed the prompt absorption of BSA at the surface or the edges of MMT by electrostatic and/or chemical interaction [42,43]. Noticeably, while the fluorescent signal measured for Trp was reproducible between different tests (small standard deviation) both in water and with Al_MMT (Figure 7A), the reproducibility between measurements was observed only in water in the case of BSA.…”
Section: Fluorescence-based Detection Of Biomolecules With Al_mmtmentioning
confidence: 93%
“…The low enhancing efficiency of Al_MMT treated with Trp can be explained by the low absorption of Trp of MMT due to the counterbalance of either positive (-NH 2 ) and negative (-COOH) groups in the aminoacidic structure. On the contrary, different studies showed the prompt absorption of BSA at the surface or the edges of MMT by electrostatic and/or chemical interaction [42,43]. Noticeably, while the fluorescent signal measured for Trp was reproducible between different tests (small standard deviation) both in water and with Al_MMT (Figure 7A), the reproducibility between measurements was observed only in water in the case of BSA.…”
Section: Fluorescence-based Detection Of Biomolecules With Al_mmtmentioning
confidence: 93%